The subtle knife - Pullman, Philip, 1946- (New York : Alfred A. Knopf, 2002)
As the boundaries between worlds begin to dissolve, Lyra and her daemon help Will Parry in his search for his father and for a powerful, magical knife.
Sequel to: The golden compass.
Keywords: Fantasy; Fantasy fiction